Objective Measures of Surgeon Non-Technical Skills in Surgery: A Scoping Review. (February 2022) - Cha, Jackie S.; Yu, Denny
Objective: The purpose of this study was to identify, synthesize, and discuss objective behavioral or physiological metrics of surgeons' nontechnical skills (NTS) in the literature. Background: NTS, or interpersonal or cognitive skills, have been identified to contribute to safe and efficient surgical performance; however, current assessments are subjective, checklist-based tools. Intraoperative skill evaluation, such as technical skills, has been previously utilized as an objective measure to address such limitations. Methods: Five databases in engineering, behavioral science, and medicine were searched following PRISMA reporting guidelines. Eligibility criteria included studies with NTS objective measurements, surgeons, and took place within simulated or live operations. Results: Twenty-three articles were included in this review. Objective metrics included communication metrics and measures from physiological responses such as changes in brain activation and motion of the eye. Frequencies of content-coded communication in surgery were utilized in 16 studies and were associated with not only the communication construct but also cognitive constructs of situation awareness and decision making. This indicates the underlying importance of communication in evaluating the NTS constructs. To synthesize the scoped literature, a framework based on the one-way communication model was used to map the objective measures to NTS constructs. Conclusion: Objective NTS measurement of surgeons is still preliminary, and future work on leveraging objective metrics in parallel with current assessment tools is needed. Application: Findings from this work identify objective NTS metrics for measurement applications in a surgical environment.